Chemical stability of doped BaCeO3-BaZrO3 solid solutions in different atmospheres - 吕敬德 王岭 樊丽华 李跃华 戴磊 (Journal of rare earths, 2008)
BaCe0.45Zr0.45M0.1O3-δ （M=Y, In） and BaCe0.9Y0.1O3-δ were prepared through the conventional solid state reaction route. The chemical stability was investigated in hydrogen, carbon dioxide, and boiling water. Crystalline phase and microsa-ucture of the proton conductor before and after stability test were measured with X-ray diffraction （XRD） and scanning electron microscopy （SEM）, respectively. The results showed that all materials were quite stable in H2 atmosphere. In CO2 atmosphere, BaCe0.45Zr0.45M0.1O3-δ（M=Y, In） were relatively stable, while Bafe0.9Y0.1O3-δ decomposed. In boiling water, BaCe0.9Y0.1O3-δ was quickly decomposed into Ba（OH）2 and corresponding oxide. BaCe0.45Zr0.45M0.1O3-δ slightly reacted with boiling water and some amorphous phases were formed. However, BaCe0.45Zr0.45In0.1O3-δ was observed to exhibit better stability than BaCe0.45Zr0.45Y0.1O3-δ in water. The experimental results were interpreted in terms of thermodynamic data and tolerance factor.